2011
DOI: 10.1016/j.jbiotec.2010.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of carotenoid production by Dunaliella salina in different culture systems and operation regimes

Abstract: The effect of operation regime and culture system on carotenoid productivity by the halotolerant alga Dunaliella salina has been analyzed. Operation strategies tested included batch and semi continuous regime, as well as a two-stage approach run simultaneously in both, open tanks and closed reactor. The best results were obtained with the closed tubular photobioreactor. The highest carotenoid production (328.8 mg carotenoid l⁻¹ culture per month) was achieved with this culture system operated following the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 22 publications
2
44
0
8
Order By: Relevance
“…The major advantages of open ponds are that they are easier to construct and operate than most closed systems. However, major limitations in open ponds include poor light utilization by the cells, evaporative losses, diffusion of CO 2 to the atmosphere, and requirement of large areas of land, contamination problems, impractical control of some environmental factors as temperature and the relatively large running costs due to the need of large volumes of water and salt (Prieto et al, 2011). Algae growth in raceways is typically assumed to require 1.5-2 kg CO 2 /kg biomass (Clarens et al, 2010) with a range of CO 2 absorption efficiencies (50-100%).…”
Section: Objectivesmentioning
confidence: 99%
“…The major advantages of open ponds are that they are easier to construct and operate than most closed systems. However, major limitations in open ponds include poor light utilization by the cells, evaporative losses, diffusion of CO 2 to the atmosphere, and requirement of large areas of land, contamination problems, impractical control of some environmental factors as temperature and the relatively large running costs due to the need of large volumes of water and salt (Prieto et al, 2011). Algae growth in raceways is typically assumed to require 1.5-2 kg CO 2 /kg biomass (Clarens et al, 2010) with a range of CO 2 absorption efficiencies (50-100%).…”
Section: Objectivesmentioning
confidence: 99%
“…D. salina had the highest carotenoid/chlorophyll ratio (2.58) at 4 M NaCl (Table 1). Prieto et al, (2011) reported that highest carotenoid production was achieved with this culture system operated following the two-stage strategy. Also they indicated that closed tubular photo-bioreactor provided the highest carotenoid contents (10% of dry weight) in , shape of D. salina grown in 4 M NaCl (stress conditions) that cell have rich β-carotene so, it is orange colour (C) and shape of D. salina grown in 2 M NaCl at optimum growth that cell have rich chlorophyll so, it is green colour (D) (Hadi, 1996).…”
Section: β-Carotenementioning
confidence: 94%
“…Dunaliella biomass and β-carotene abundance (90% of total carotenoids) as well as the highest 9-cis to all-trans β-carotene isomer ratio (Prieto et al, 2011). In addition, Hosseini reported that Iranian strain G of Dunaliella salina had the highest potential for β-carotene accumulation and suitable for outdoor cultivation (Fig.…”
Section: β-Carotenementioning
confidence: 99%
“…The hexane layer was separated and its absorbance at 450nm, 662nm and 645nm. Total carotene: A 450 × 25.2 equal the micrograms of carotene in sample [32,36]. Chl a and Chl b contents were estimated according to Lichtenthaler and Wellburn [20]: …”
Section: Total Carotene and Chlorophyllsmentioning
confidence: 99%
“…In D. bardawil, increasing light intensity and light period or inhibiting growth by various stress conditions such as nutrient deficiency or high salt concentration caused a decrease in the content of chlorophyll per cell and an increase in the amount of β-carotene per cell and the β-carotene-to-chlorophyll ratio [4]. β-carotene accumulation of Dunaliella salina is enhanced up to 10% of the alga dry weight under several conditions: high irradiance, stress temperatures, high salt concentration and/or nutrient deficiency [7,32].…”
Section: Carotenoid Content Of Dunaliella Salina A9mentioning
confidence: 99%